Audel guide to the 2005 National Electrical Code - Rosenberg, Paul, 1958- (Wiley, 2004)
Here's what you need to knowUnderstanding and following the voluminous National Electrical Code is a constant challenge. You need a reference that doesn't waste your time. This guide extracts the information necessary for you, the installer, then arranges it for easy access and highlights the changes so you can quickly spot what's new. Whether you're a novice or a veteran, you'll want this book with you on every job.* Understand the terms and rules for installation set forth in the NEC* Identify what's new in the 2005 version* Review each section of the NEC that applies to.